Sustainability in Project Management - Laura TRIFAN; Anastasia STANILOIU (Communications of International Proceedings, 2021)
The paper highlights the stationary importance of Project Management and its increasing role in a fast-developing project environment, where integrated information is essential, and the coordinated information flow makes the difference in solving problems and creating value. The economy might be seen as a Project Economy and the Project Management as a global profession. The mutual influence of organizing existing projects and creating new ideas by project management is a determination that is analyzed here, consistently searching for the harmonization between general and particular aspects of projects and the more and more imperative requirements of the sustainable development. The knowledge-based society has to deal with two opposite tendencies: the generalization and synthetic structuring of each endeavor versus the particularization in myriads of adapted forms of manifestation of ideas for each type of industrial, economic, and social activity. Today´s tools of dealing with necessary information for new projects and the composition of the project portfolio are more complex than those of the past, when networking, internationalization and digitalization were not yet operational and the best fitting approach for the project processing is the agile project management and the agile thinking. Some modern Project management tools and their applications are presented in the paper together with the criteria of choosing adequate tools for the project execution based on practical examples of non-IT projects and IT projects for SMEs.
Keywords: Project Management; Sustainable Development; Project Management Tools; Optimization; Agile Project Management; Devops Example